Pendampingan Desa Wisata Garongan: Program Kerjasama Sekolah Tinggi Pariwisata AMPTA Yogyakarta dengan Kementrian Pariwisata dan Ekonomi Kreatif - Hary Hermawan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
Mentoring of Garongan Tourism Village: Sekolah Tinggi Pariwisata AMPTA Yogyakarta Collaboration Program with the Kementrian Pariwisata dan Ekonomi Kreatif/ Badan Pariwisata dan Ekonomi Kreatif. Garongan Tourism Village is one of the developing tourism villages in the Yogyakarta Special Region. Garongan Tourism Village has tourism potential, including natural tourism, cultural tourism, culinary tourism. This village also has an interesting historical background as a former hiding place for thieves (Garong: Java). There are still weaknesses in the management of Garongan Tourism Village and the many tourism potentials that exist, so that this village needs improvement through the tourism village assistance program. This mentoring program results from the collaboration between the Sekolah Tinggi Pariwisata AMPTA Yogyakarta and the Kementrian Pariwisata dan Ekonomi Kreatif/Badan Pariwisata dan Ekonomi Kreatif. Mentoring results are measured by indicators of success, showing that the capacity of human resources and governance of the Garongan Tourism Village has increased. This mentoring program also resulted in the achievement of the Sekolah Tinggi Pariwisata AMPTA Yogyakarta as the best tourism village mentoring in the top 14 National ranks by the Kementrian Pariwisata dan Ekonomi Kreatif/Badan Pariwisata dan Ekonomi Kreatif.